Polymers and their applications, compositions for encapsulating glue, method for preparing encapsulating glue
Patent Information
- Application Number
- CN202410860675.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-28
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-06-28
AI Technical Summary
[0005]本发明要解决的技术问题在于克服现有技术中的对可见光透光率低,光转化材料对紫外线的吸收较差,将紫外线转化为可见光的效率较低,且耐候性差的问题
[0088]1. The polymer of the present invention can be used as an ultraviolet light conversion agent; the ultraviolet light conversion encapsulation film prepared using the polymer of the present invention can absorb ultraviolet light and convert it into visible light, thereby reducing the transmittance of ultraviolet light, and the ultraviolet light conversion encapsulation film has high permeability, which can increase the transmittance of visible light.
Smart Images

Figure CN121248898B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of solar cells, and more specifically to polymers and their applications, compositions for encapsulating adhesives, and methods for preparing encapsulating adhesives. Background Technology
[0002] With environmental degradation, ultraviolet radiation is increasingly affecting humans. In the field of solar cells, some cells age severely after exposure to ultraviolet radiation, especially heterojunction modules. Their high photoelectric conversion efficiency largely stems from the excellent surface passivation ability of intrinsic amorphous silicon over crystalline silicon. However, the TCO film and amorphous silicon film absorb ultraviolet radiation, resulting in lower current than ordinary cells and causing power degradation. Therefore, heterojunction modules have high requirements for UV resistance. Although ultraviolet cut-off layers and ultraviolet absorbers can block ultraviolet radiation from reaching the module, they also reduce the module's light conversion efficiency. Therefore, in the photovoltaic field, it is necessary not only to prevent ultraviolet radiation aging of solar cell modules but also to have high-transmittance films in the visible light region while simultaneously improving the photoelectric conversion efficiency of the modules.
[0003] Light conversion agents are products that absorb negative gain light and convert it into positive gain light. They are added as additives or auxiliaries to encapsulant films to form light conversion films. They not only absorb ultraviolet light but also convert the absorbed ultraviolet light into visible light. The functional principle of light conversion agents is that after the material absorbs energy of a certain wavelength, electrons are excited to an excited state, which is a high-energy state. This energy can be transferred to the central ion, causing its electrons to transition from the unstable high-energy state back to the stable ground state. During this return process, the energy is released in the form of light, thus achieving light conversion. However, existing encapsulation materials have low visible light transmittance, poor ultraviolet absorption, and low efficiency in converting ultraviolet light into visible light, thus limiting their improvement on the conversion efficiency and weather resistance of solar cells.
[0004] Therefore, it is particularly urgent to develop ultraviolet light converters with high transmittance, the ability to absorb ultraviolet light and convert it into visible light with high efficiency, and high weather resistance. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to overcome the problems of low visible light transmittance, poor absorption of ultraviolet light by light conversion materials, low efficiency of converting ultraviolet light into visible light, and poor weather resistance in the prior art.
[0006] To achieve the above objectives, a first aspect of the present invention provides a triazole-containing polymer having the structure shown in formula (I).
[0007]
[0008] In equation (I),
[0009] n is an integer between 1 and 100;
[0010] X is -O-, -S-, -Se-, -S(O)2-, or -NR x -;R x Selected from C 1-12 Any one of alkyl, phenyl, and benzyl groups;
[0011] R1 is selected from C 2-12 Alkyl, unsubstituted C 3-8 cycloalkyl, composed of C 1-6 At least one group in the alkyl group substituted with C 4-12 3-6 membered cycloalkyl groups;
[0012] R 21 R 22 R 23 R 24 R 25 Each is independently selected from H, hydroxyl, and C. 1-12 alkyl groups, C groups substituted with at least one group from combination A 1-12 alkyl, C 1-12 alkoxy groups, R3COO-, R3CO-, C 2-12 At least one of alkenyl, (R3O)3Si-, and (R3O)3SiO-, where R3 is selected from C 1-12 alkyl, C 2-12 Any one of the alkenyl groups; the combination A consists of a halogen, a 3-6 membered cycloalkyl group containing at least one heteroatom selected from at least one of O, S, and N.
[0013] A second aspect of the invention provides the use of the polymer described in the first aspect in encapsulating adhesives.
[0014] A third aspect of the present invention provides a composition for encapsulating adhesive, the composition comprising 100 parts by weight of a matrix material, 0.005-2 parts by weight of an ultraviolet light converter, 0-2 parts by weight of a photoinitiator, 0.1-1 parts by weight of a light stabilizer, 0-3 parts by weight of a crosslinking agent, 0-2 parts by weight of a co-crosslinking agent, 0.05-1 parts by weight of an antioxidant, and 0.2-1 parts by weight of a silane coupling agent; wherein the ultraviolet light converter is selected from the polymers described in the first aspect of the present invention.
[0015] A fourth aspect of the present invention provides a method for preparing an encapsulating adhesive, the method comprising: curing a material I containing each component of a composition to obtain the encapsulating adhesive; wherein the composition is the encapsulating adhesive composition described in the third aspect.
[0016] The novel polymer developed in this invention not only improves the transmittance of visible light and promotes the absorption of visible light by solar cells, but also increases the conjugated system by introducing olefin molecules containing carbon-carbon double bonds, thereby increasing the radiative transition rate and efficiently converting the absorbed ultraviolet light into visible light for radiation, further improving the photoelectric conversion efficiency.
[0017] The polymer of this invention is added to the film as an ultraviolet light conversion encapsulation film, which is applied to solar cell modules. It has high visible light transmittance, good absorption of ultraviolet light, and converts ultraviolet light into visible light, thereby significantly improving the conversion efficiency and weather resistance of solar photovoltaic modules. Detailed Implementation
[0018] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0019] In this invention, unless otherwise specified, groups of the same type have similar interpretations, and will not be described in detail here.
[0020] C 1-12 The alkyl group refers to a straight-chain alkyl or branched alkyl group with a total number of carbon atoms of 1-12 (e.g., 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12). For example, it can be methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, etc.
[0021] Unreplaced C 3-8 The cycloalkyl group is defined as having 3-8 carbon atoms in the cycloalkyl group (e.g., 3, 4, 5, 6, 7, 8) and containing no substituents.
[0022] By C 1-6 At least one group in the alkyl group substituted with C 4-12 The 3-6 membered cycloalkyl group indicates that the total number of carbon atoms in the cycloalkyl group is 4-12 (e.g., 4, 5, 6, 7, 8, 9, 10, 11, 12), the number of cyclic atoms on the cycloalkyl group is 3-6 (e.g., 3, 4, 5, 6), and the cycloalkyl group has at least one substituent, which is a C14 group. 1-6 At least one of the alkyl groups.
[0023] C 2-12The alkenyl group refers to a straight-chain alkenyl or branched alkenyl group with a total number of carbon atoms of 2-12 (e.g., 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12). The group contains a double bond, and there are no specific requirements for the position of the double bond. It can be at the end of the group, in the middle, or at the beginning (indicating the position where it is connected to the parent nucleus structure).
[0024] As previously described, a first aspect of the present invention provides a triazole-containing polymer having the structure shown in formula (I).
[0025]
[0026] In equation (I),
[0027] n is an integer between 1 and 100;
[0028] X is -O-, -S-, -Se-, -S(O)2-, or -NR x -;R x Selected from C 1-12 Any one of alkyl, phenyl, and benzyl groups;
[0029] R1 is selected from C 2-12 Alkyl, unsubstituted C 3-8 cycloalkyl, composed of C 1-6 At least one group in the alkyl group substituted with C 4-12 3-6 membered cycloalkyl groups;
[0030] R 21 R 22 R 23 R 24 R 25 Each is independently selected from H, hydroxyl, and C. 1-12 alkyl groups, C groups substituted with at least one group from combination A 1-12 alkyl, C 1-12 alkoxy groups, R3COO-, R3CO-, C 2-12 At least one of alkenyl, (R3O)3Si-, and (R3O)3SiO-, where R3 is selected from C 1-12 alkyl, C 2-12 Any one of the alkenyl groups; the combination A consists of a halogen, a 3-6 membered cycloalkyl group containing at least one heteroatom selected from at least one of O, S, and N.
[0031] For example, n is 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 5 1, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99 or 100.
[0032] Preferably, the polymer having the structure shown in formula (I) has a weight-average molecular weight of 0.1 million to 100,000; more preferably 0.15 million to 50,000; even more preferably 0.2 million to 20,000; and even more preferably 0.3 million to 15,000.
[0033] In the preferred case, in equation (I),
[0034] n is an integer between 2 and 90;
[0035] X is -O-, -S-, -Se-, -S(O)2-, or -NR x -;R x Selected from C 1-10 Any one of alkyl, phenyl, and benzyl groups;
[0036] R1 is selected from C 2-10 Alkyl, unsubstituted C 3-6 cycloalkyl, composed of C 1-6 At least one group in the alkyl group substituted with C 4-10 3-6 membered cycloalkyl groups;
[0037] R 21 R 22 R 23 R 24 R 25 Each is independently selected from H, hydroxyl, and C. 1-12 alkyl groups, C groups substituted with at least one group from combination A 1-12 alkyl, C 1-12 alkoxy groups, R3COO-, R3CO-, C 2-12 At least one of alkenyl, (R3O)3Si-, and (R3O)3SiO-, where R3 is selected from C 1-10 alkyl, C 2-10Any one of the alkenyl groups; the combination A consists of fluorine, chlorine, bromine, or a 3-6 membered cycloalkyl group containing at least one O atom as a cycloforming atom.
[0038] According to a preferred embodiment (hereinafter referred to as preferred embodiment 1), in formula (I),
[0039] n is 4, 5, 6, 7 or 8;
[0040] X is either -O- or -S-;
[0041] R1 is selected from C 2-10 Alkyl, unsubstituted C 3-6 cycloalkyl, composed of C 1-6 At least one group in the alkyl group substituted with C 4-10 3-6 membered cycloalkyl groups;
[0042] R 21 R 22 R 23 R 24 R 25 Each is independently selected from H, hydroxyl, and C. 1-12 alkyl groups, C groups substituted with at least one group from combination A 1-12 alkyl, C 1-12 alkoxy groups, R3COO-, R3CO-, C 2-12 At least one of alkenyl, (R3O)3Si-, and (R3O)3SiO-, where R3 is selected from C 1-10 alkyl, C 2-10 Any one of the alkenyl groups; the combination A consists of fluorine, chlorine, bromine, or a 3-6 membered cycloalkyl group containing at least one O atom as a cycloforming atom.
[0043] In the preferred embodiment 1, more preferably, the polymer represented by formula (I) is selected from any one of the following, wherein each of n is independently 4, 5, 6, 7 or 8:
[0044]
[0045]
[0046] According to a preferred embodiment (hereinafter referred to as preferred embodiment 2), in formula (I),
[0047] n is 4, 5, 6, 7 or 8;
[0048] X is either -Se- or -S(O)2-;
[0049] R1 is selected from C 2-10 Alkyl, unsubstituted C3-6 cycloalkyl, composed of C 1-6 At least one group in the alkyl group substituted with C 4-10 3-6 membered cycloalkyl groups;
[0050] R 21 R 22 R 23 R 24 R 25 Each is independently selected from H, hydroxyl, and C. 1-12 alkyl groups, C groups substituted with at least one group from combination A 1-12 alkyl, C 1-12 alkoxy groups, R3COO-, R3CO-, C 2-12 At least one of alkenyl, (R3O)3Si-, and (R3O)3SiO-, where R3 is selected from C 1-10 alkyl, C 2-10 Any one of the alkenyl groups; the combination A consists of fluorine, chlorine, bromine, or a 3-6 membered cycloalkyl group containing at least one O atom as a cycloforming atom.
[0051] In a preferred embodiment 2, more preferably, the polymer represented by formula (I) is selected from any one of the following, wherein n is independently 4, 5, 6, 7 or 8:
[0052]
[0053]
[0054] According to a preferred embodiment (hereinafter referred to as preferred embodiment 3), in formula (I),
[0055] n is 4, 5, 6, 7 or 8;
[0056] X is -NR x -;R x Selected from C 1-10 Any one of alkyl, phenyl, and benzyl groups;
[0057] R1 is selected from C 2-10 Alkyl, unsubstituted C 3-6 cycloalkyl, composed of C 1-6 At least one group in the alkyl group substituted with C 4-10 3-6 membered cycloalkyl groups;
[0058] R 21 R 22 R 23 R 24 R 25 Each is independently selected from H, hydroxyl, and C. 1-12alkyl groups, C groups substituted with at least one group from combination A 1-12 alkyl, C 1-12 alkoxy groups, R3COO-, R3CO-, C 2-12 At least one of alkenyl, (R3O)3Si-, and (R3O)3SiO-, where R3 is selected from C 1-10 alkyl, C 2-10 Any one of the alkenyl groups; the combination A consists of fluorine, chlorine, bromine, or a 3-6 membered cycloalkyl group containing at least one O atom as a cycloforming atom.
[0059] In a preferred embodiment 3, more preferably, the polymer represented by formula (I) is selected from any one of the following, wherein n is independently 4, 5, 6, 7 or 8:
[0060]
[0061] According to a particularly preferred embodiment, the polymer represented by formula (I) is selected from any one of the following, wherein each of n is independently 4, 5, 6, 7 or 8:
[0062]
[0063]
[0064]
[0065] This invention does not impose any particular limitation on the specific methods for preparing the aforementioned polymers. Those skilled in the art can obtain the aforementioned polymers of this invention by combining the specific structural formulas provided by this invention with conventional process routes in the field of organic synthesis. Furthermore, several examples are exemplarily listed below to illustrate the preparation methods of the polymers of this invention. Those skilled in the art can also obtain specific preparation methods for all other polymers by changing the types of raw materials according to the preparation methods of the polymers described below. This invention will not further describe the preparation methods of all polymers in detail, and this should not be construed as a limitation of the invention.
[0066] As previously stated, a second aspect of the present invention provides the use of the polymer described in the first aspect in encapsulating adhesives.
[0067] In a preferred embodiment, the encapsulating adhesive is an ultraviolet light conversion encapsulating adhesive.
[0068] As previously described, a third aspect of the present invention provides a composition for encapsulating adhesive, the composition comprising 100 parts by weight of a matrix material, 0.005-2 parts by weight of an ultraviolet light converter, 0-2 parts by weight of a photoinitiator, 0.1-1 parts by weight of a light stabilizer, 0-3 parts by weight of a crosslinking agent, 0-2 parts by weight of a co-crosslinking agent, 0.05-1 parts by weight of an antioxidant, and 0.2-1 parts by weight of a silane coupling agent;
[0069] The ultraviolet light converter is selected from the polymers described in the first aspect.
[0070] Preferably, the matrix material is an ethylene copolymer. More preferably, the ethylene copolymer is any one or a mixture of at least two of the following: ethylene-vinyl acetate copolymer, ethylene-butene copolymer, ethylene-octene copolymer, ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer, ethylene-vinyl acetate-based multi-component copolymer, ethylene-methyl acrylate-based multi-component copolymer, ethylene-ethyl acrylate-based multi-component copolymer, ethylene-methyl methacrylate-based multi-component copolymer, ethylene-ethyl methacrylate-based multi-component copolymer, and ethylene-α-olefin copolymer.
[0071] Particularly preferred is that the matrix material is an ethylene-vinyl acetate copolymer.
[0072] More preferably, the vinyl acetate structural unit content in the ethylene-vinyl acetate copolymer used as the matrix material is 25-35 wt%, the melt index of the ethylene-vinyl acetate copolymer is 0.1-40 g / min, the melting point is 40-90℃ (under the test conditions of 190℃ / 2.16kg), and the light transmittance is ≥90%.
[0073] Preferably, the photoinitiator is selected from: 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexylphenyl ketone, benzophenone, (2,4,6-trimethylbenzoyl)diphenylphosphine oxide, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone, 2-hydroxy-2-methyl-1-phenylpropanone (2-hydroxy-1-(4-(2-hydroxy-2-methylpropionylphenyl)benzyl)-2-methyl-1-propanone, titanoceramsite photoinitiators, thiopyridinone / iodonium salt systems, organic peroxide systems, borate / dye systems, hexaaryl diimidazole / dye systems, coumarin ketone / dye systems, benzoyl ketal photoinitiators, acetophenone photoinitiators, anthraquinone photoinitiators and their derivatives, benzoate photoinitiators, bicyclic diketone compounds, camphorquinone, any one or a mixture of at least two of the following.
[0074] Preferably, the light stabilizer is selected from one or a mixture of at least two of the following: bis(2,2,6,6-tetramethyl-4-piperidinol) sebacate, bis-2,2,6,6-tetramethylpiperidinol sebacate, 2-(2'-hydroxy-5'-methylphenyl)-benzotriazole, [[3,5-di-tert-butyl-4-hydroxyphenyl]methyl]butylmalonate di(1,2,2,6,6-pentamethyl-4-piperidinol), bis(2,2,6,6-tetramethyl-4-piperidinol) sebacate, and 2,4-dichloro-6-(4-morpholino)-1,3,5-triazine.
[0075] Preferably, the crosslinking agent is selected from: tert-butyl peroxide, tert-butyl peroxide-isopropyl carbonate, cyclohexanone peroxide, tert-butyl hydrogen peroxide, dicumyl peroxide, di(tert-butyl peroxide-isopropyl)benzene, benzoyl peroxide, di(2,4-dichlorobenzoyl peroxide), tert-butyl peroxybenzoate, tert-butyl peroxycarbonate-2-ethylhexyl peroxide, tert-butyl peracetate, tert-butyl peroxide-3,5,5-trimethylhexanoate, di(4-tert-butylcyclohexanone) peroxybicarbonate, tert-amyl peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, 1,1-di-tert-butyl peroxycyclohexane, and 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, or a mixture of at least two of the following.
[0076] Preferably, the crosslinking agent is selected from one or a mixture of at least two of the following: triallyl isocyanurate, ethylene glycol dimethacrylate, N,N′-m-phenylbismaleimide, trimethylolpropane trimethacrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, propanetriol triacrylate, and ethoxylated pentaerythritol tetraacrylate.
[0077] Preferably, the antioxidant is selected from one or a mixture of at least two of the following: 2,6-di-tert-butyl-p-cresol, di(2,4-dicumylphenyl)pentaerythritol diphosphite, distearate pentaerythritol diphosphite, β-(3,5-di-tert-butyl-4-hydroxybenzyl)propionate, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanuric acid, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate n-octadecyl alcohol, tetrakis(β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate)pentaerythritol ester, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), tetrakis(2,4-di-tert-butylphenyl-4,4'-biphenyl) diphosphite, tris(2,4-di-tert-butylphenyl) phosphite, and tris(nonylphenyl) phosphite.
[0078] Preferably, the silane coupling agent is selected from one or a mixture of at least two of the following: vinyltriethoxysilane, vinyltrimethoxysilane, vinyltri(2-methoxyethoxy)silane, 3-triethoxysilyl-1-propylamine, (triethoxysilyl)ethylene, γ-glycidoxypropyltrimethoxysilane, vinyltrichlorosilane, γ-methacryloyloxypropyltrimethoxysilane, γ-methacryloyloxypropyltriisopropoxysilane, 3-thiopropyltrimethoxysilane, and 3-thiopropyltriethoxysilane.
[0079] As previously stated, a fourth aspect of the present invention provides a method for preparing an encapsulating adhesive, the method comprising: curing a material I containing each component of a composition to obtain the encapsulating adhesive; wherein the composition is the encapsulating adhesive composition described in the third aspect.
[0080] In a more preferred embodiment, the curing process includes: sequentially mixing and casting the material I.
[0081] Preferably, the mixing temperature is 70℃~120℃; the mixing time is 10min-40min; and the mixing speed is 100r / min~300r / min.
[0082] Preferably, the thickness of the encapsulating film obtained after casting is 0.3 mm to 0.8 mm. More preferably, the thickness of the ultraviolet light conversion encapsulating film is 0.5 mm.
[0083] Optionally, the casting process is carried out in a casting machine, through plasticizing extrusion, stretching, traction, and winding, to obtain the encapsulating adhesive (film).
[0084] The present invention also provides a photovoltaic module comprising an encapsulating adhesive (film) prepared by the above-described preparation method.
[0085] Preferably, the method for preparing the photovoltaic module provided by the present invention includes the following steps: stacking photovoltaic glass, the above-mentioned encapsulating adhesive (film), solar cells, encapsulating adhesive (film), and photovoltaic backsheet in sequence, and then heating and pressing to obtain the photovoltaic module.
[0086] Preferably, during the heating and pressing process, the heating temperature is 80-170℃, the pressing pressure is 40KPa-70KPa, and the pressing time is 15-30min.
[0087] The technical solution of the present invention has at least the following advantages:
[0088] 1. The polymer of the present invention can be used as an ultraviolet light conversion agent; the ultraviolet light conversion encapsulation film prepared using the polymer of the present invention can absorb ultraviolet light and convert it into visible light, thereby reducing the transmittance of ultraviolet light, and the ultraviolet light conversion encapsulation film has high permeability, which can increase the transmittance of visible light.
[0089] 2. The polymer of the present invention, as an ultraviolet light conversion agent, can increase the absorption of ultraviolet light. After absorbing ultraviolet light, it transfers energy to the light-emitting unit through intramolecular charge transfer, and then converts it into visible light radiation, thereby promoting the absorption of visible light by the solar cell and improving the photoelectric conversion efficiency of the photovoltaic module.
[0090] 3. The polymer of the present invention can increase the stability of the ultraviolet light conversion encapsulation film, thereby reducing the brightness decay rate of the ultraviolet light conversion encapsulation film containing the polymer, and thus improving the weather resistance of the photovoltaic module.
[0091] The present invention will be described in detail below through examples. In the following examples, unless specific experimental steps or conditions are specified, the procedures or conditions described in conventional experimental procedures in the literature of the art can be followed. Reagents or instruments whose manufacturers are not specified are all commercially available conventional reagent products.
[0092] Unless otherwise specified, room temperature as mentioned below refers to 25±1℃.
[0093] The ethylene-vinyl acetate copolymer used in this invention has a vinyl acetate structural unit content of 28 wt%, a melt index of 20 g / 10 min (under test conditions of 190 °C / 2.16 kg), and a melting point of 75 °C.
[0094] Preparation Example 1: Synthesis of Polymer 2
[0095]
[0096] Synthesis of intermediate 2-1: In a Schlenk tube, under a nitrogen atmosphere, 0.1 mol of 4,7-dibromo-2-isobutyl-2H-benzo[d][1,2,3]triazole, 0.1 mol of 2,8-bis(4,4,5,5-tetramethyl-1,3,2-dioxoboronyl-2-yl)dibenzo[b,d]furan, 0.005 mol of methanesulfonic acid (tri-tert-butylphosphino)(2'-methylamino-1,1'-biphenyl-2-yl)palladium(II)(Pd-P(-Bu)-G4), 0.22 mol of potassium trimethylsilanolate (TMSOK), and 5 mL of dry toluene (0.05 M) were added. The reaction mixture was then stirred at 25 °C for 24 hours to give intermediate 2-1 (yield: 61%).
[0097] Synthesis of intermediate 2-2: 0.06 mol of intermediate 2-1 was dissolved in 140 mL of toluene solvent, and nitrogen gas was introduced and stirred. 0.06 mol of 2-(4-methoxyphenyl)-4,4,5,5-tetramethyl-1,3,2-dioxoborane, 0.3 mol of potassium carbonate, and 0.36 mmol of tetra(triphenylphosphine)palladium were added sequentially. The mixture was heated to reflux. After 6 h, HPLC analysis showed that the starting material had basically reacted completely. The reaction was stopped, and the mixture was cooled and filtered to obtain the crude product. The crude product was completely dissolved in toluene, and the filtrate was evaporated to dryness under reduced pressure. The residue was subjected to column chromatography to obtain intermediate 2-2 (yield: 68%).
[0098] Synthesis of intermediate 2-3: The synthesis method is the same as that of intermediate 2-2, to obtain intermediate 2-3 (yield: 61%).
[0099] Synthesis of Polymer 2: 0.01 mol of intermediate 2-3 was dissolved in 20 mL of dichloromethane, cooled to 0 °C, and 0.013 mol of boron tribromide was added. The mixture was stirred at 0 °C for 24 h. After the reaction was completed, sodium bicarbonate aqueous solution was added to quench the reaction, and then the mixture was extracted three times with dichloromethane. After drying with anhydrous magnesium sulfate, the reaction solution was evaporated to dryness under reduced pressure and polymer 2 was obtained by column chromatography (yield: 66%, n = 4-6).
[0100] Preparation Example 2: Synthesis of Polymer 19
[0101]
[0102] Synthesis of intermediate 19-1: The synthesis method of intermediate 2-1 is the same as that of intermediate 19-1, to obtain intermediate 19-1 (yield: 57%).
[0103] Synthesis of intermediate 19-2: The synthesis method is the same as that of intermediate 2-2, yielding intermediate 19-2 (yield: 65%).
[0104] Synthesis of polymer 19: The synthesis method is the same as that of intermediate 2-2, yielding polymer 19 (yield: 67%, n = 6-8).
[0105] Preparation Example 3: Synthesis of Polymer 42
[0106]
[0107] Synthesis of intermediate 42-1: The synthesis method of intermediate 2-1 is the same as that of intermediate 42-1, to obtain intermediate 42-1 (yield: 60%).
[0108] Synthesis of intermediate 42-2: The synthesis method is the same as that for intermediate 2-2, yielding intermediate 42-2 (yield: 62%).
[0109] Synthesis of polymer 42: The synthesis method is the same as that of intermediate 2-2, yielding polymer 42 (yield: 63%, n = 5-7).
[0110] Preparation Example 4: Synthesis of Polymer 51
[0111]
[0112] Synthesis of intermediate 51-1: 0.1 mol of 2,4-dimethyl-3-pentanol was dissolved in 110 mL of dichloromethane, and trifluoromethanesulfonic anhydride was added dropwise. The reaction was carried out at room temperature for 5 h. The organic phase was evaporated to dryness under reduced pressure, and the residue was subjected to column chromatography to obtain intermediate 51-1 (yield: 64%).
[0113] Synthesis of intermediate 51-2: 0.05 mol of 4,7-dibromo-2H-benzo[d][1,2,3]triazole was dissolved in 140 mL of toluene. 0.05 mol of intermediate 51-1, 0.125 mol of sodium tert-butoxide, 0.15 mmol of tris(dibenzylideneacetone)dipalladium, and 0.15 mmol of tritert-butylphosphine were added. The mixture was stirred under nitrogen atmosphere and heated to reflux. After 4 h, the reaction was confirmed to be complete. The reaction solution was evaporated to dryness under reduced pressure and intermediate 51-2 was obtained by column chromatography (yield: 61%).
[0114] Synthesis of intermediate 51-3: The synthesis method of intermediate 2-1 is the same, to obtain intermediate 51-3 (yield: 56%).
[0115] Synthesis of intermediate 51-4: The synthesis method is the same as that of intermediate 2-2, to obtain intermediate 51-4 (yield: 62%).
[0116] Synthesis of polymer 51: The synthesis method is the same as that of intermediate 2-2, to obtain polymer 51 (yield: 65%, n = 6-8).
[0117] Preparation Example 5: Synthesis of Polymer 57
[0118]
[0119] Synthesis of intermediate 57-1: The synthesis method of intermediate 51-1 is the same as that of intermediate 57-1, to obtain intermediate 57-1 (yield: 63%).
[0120] Synthesis of intermediate 57-2: The synthesis method of intermediate 51-2 is the same as that of intermediate 57-2, and intermediate 57-2 is obtained (yield: 66%).
[0121] Synthesis of intermediate 57-3: The synthesis method of intermediate 2-1 is the same, to obtain intermediate 57-3 (yield: 52%).
[0122] Synthesis of intermediate 57-4: The synthesis method is the same as that for intermediate 2-2, yielding intermediate 57-4 (yield: 68%).
[0123] Synthesis of polymer 57: The synthesis method is the same as that of intermediate 2-2, yielding polymer 57 (yield: 69%, n = 4-6).
[0124] Preparation Example 6: Synthesis of Polymer 60
[0125]
[0126] Synthesis of intermediate 60-1: The synthesis method of intermediate 51-1 is the same as that of intermediate 60-1, to obtain intermediate 60-1 (yield: 60%).
[0127] Synthesis of intermediate 60-2: The synthesis method of intermediate 51-2 is the same as that of intermediate 60-2, to obtain intermediate 60-2 (yield: 64%).
[0128] Synthesis of intermediate 60-3: The synthesis method of intermediate 2-1 is the same, to obtain intermediate 60-3 (yield: 51%).
[0129] Synthesis of intermediate 60-4: The synthesis method is the same as that for intermediate 2-2, yielding intermediate 60-4 (yield: 69%).
[0130] Synthesis of polymer 60: The synthesis method is the same as that of intermediate 2-2, yielding polymer 60 (yield: 66%, n = 5-7).
[0131] Preparation Example 7: Synthesis of Polymer 63
[0132]
[0133] Synthesis of intermediate 63-1: The synthesis method of intermediate 2-1 is the same as that of intermediate 63-1, yielding intermediate 63-1 (yield: 52%).
[0134] Synthesis of intermediate 63-2: The synthesis method is the same as that for intermediate 2-2, yielding intermediate 63-2 (yield: 67%).
[0135] Synthesis of polymer 63: The synthesis method is the same as that for intermediate 2-2, yielding polymer 63 (yield: 63%, n = 6-8).
[0136] Preparation Example 7: Synthesis of Polymer 72
[0137]
[0138] Synthesis of intermediate 72-1: The synthesis method is the same as that of intermediate 2-2, yielding intermediate 72-1 (yield: 66%).
[0139] Synthesis of polymer 72: The synthesis method is the same as that for intermediate 2-2, yielding polymer 72 (yield: 68%, n = 4-6).
[0140] Example of encapsulating film:
[0141] The preparation method of the encapsulating film includes the following steps:
[0142] The matrix material, UV conversion agent, photoinitiator, light stabilizer, crosslinking agent, co-crosslinking agent, antioxidant, and silane coupling agent are mixed evenly in a mixing tank and then fed into a twin-screw extruder. The mixture is kneaded at 90°C and 200 rpm. Afterward, it undergoes plasticizing extrusion, stretching, traction, and winding in a casting machine to obtain a 0.5 mm thick UV conversion encapsulating film. For specific examples, please refer to the encapsulating film examples and comparative examples.
[0143] Example 1 of encapsulating film:
[0144] This embodiment provides an ultraviolet light conversion encapsulating film, prepared using the above-described preparation method. The base material is 100g of ethylene-vinyl acetate copolymer, the ultraviolet light converter is 0.1g of polymer 2, the photoinitiator is 1g of 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone, the light stabilizer is 0.1g of 2,4-dichloro-6-(4-morpholino)-1,3,5-triazine, the crosslinking agent is 0.5g of dicumyl peroxide, the co-crosslinking agent is 0.5g of triallyl isocyanurate, the antioxidant is 0.05g of tri(nonylphenyl) phosphite, and the silane coupling agent is 0.2g of 3-thiopropyltriethoxysilane.
[0145] Example 2 of encapsulating film:
[0146] This embodiment provides an ultraviolet light conversion encapsulating film, prepared using the same method as in encapsulating film embodiment 1, except that the ultraviolet light converter in this embodiment is 0.05g of polymer 2. Everything else is the same as in encapsulating film embodiment 1.
[0147] Example 3 of encapsulating film:
[0148] This embodiment provides an ultraviolet light conversion encapsulating film, prepared using the same method as in encapsulating film embodiment 1, except that the ultraviolet light converter in this embodiment is 0.3g of polymer 2. Everything else is the same as in encapsulating film embodiment 1.
[0149] Example 4 of encapsulating film:
[0150] This embodiment provides an ultraviolet light conversion encapsulation film, which is prepared using the same method as the encapsulation film in Embodiment 1, except that:
[0151] In this embodiment, the silane coupling agent is 0.2g of γ-methacryloxypropyltriisopropoxysilane (that is, the same weight of γ-methacryloxypropyltriisopropoxysilane is used to replace 3-thiopropyltriethoxysilane in encapsulation film embodiment 1), and the rest are the same as in encapsulation film embodiment 1.
[0152] Encapsulation film examples 5-15:
[0153] Encapsulation films Examples 5 to 15 were prepared using a method similar to that used in Encapsulation Film Example 1, except that polymer 2 in Encapsulation Film Example 1 was replaced with the polymer listed in Table 1.
[0154] Comparative Examples of Encapsulating Films 1-3:
[0155] Comparative Examples 1-3 of encapsulating films were prepared using a method similar to that used in Example 1 of the encapsulating film. The difference was that polymer 2 in Example 1 of the encapsulating film was replaced with Ref1, Ref2, and Ref3 respectively. The synthesis methods of Ref1 and Ref2 were the same as those of polymer 2, and n was 4-6 for each.
[0156]
[0157] Test case
[0158] Performance tests were performed on the ultraviolet light conversion encapsulating films obtained in Examples 1-15 and Comparative Examples 1-3:
[0159] The transmittance test standard is in accordance with GB / T29848-2018. The transmittance test is conducted using a specific ultraviolet-visible spectrophotometer (PerkinElmer LAMBDA950); the test is performed in the visible light band.
[0160] UV aging resistance test: Tested according to IEC 61215 standard. Test conditions: Sample area 12cm*6cm, irradiance 120W / m². 2 The test was conducted for 1440 hours under the following conditions: temperature 85℃, humidity 85%. The rate of brightness decay compared to the initial brightness was measured. Brightness decay rate % = brightness after aging / initial brightness * 100%.
[0161] Photovoltaic modules comprising encapsulating film Examples 1-14 and encapsulating film Comparative Examples 1-3 were tested for photoelectric conversion efficiency. The photovoltaic modules were prepared as follows: photovoltaic glass, ultraviolet conversion encapsulating film, solar cells, ultraviolet conversion encapsulating film, and photovoltaic backsheet were neatly stacked and placed in a laminator for lamination at 100°C for 20 minutes at a lamination pressure of 60 kPa. The modules were then removed and cooled to obtain the photovoltaic modules. (The two ultraviolet conversion encapsulating films in the same photovoltaic module are of the same type).
[0162] Photovoltaic conversion efficiency test: A standard sunlight beam was emitted using a solar simulator for testing (spectral AM 1.5G, incident power 100mW / cm²). 2 (Temperature 25℃).
[0163] The test results are shown in Table 1.
[0164] The method for calculating the photoelectric conversion efficiency improvement rate in Table 1 is as follows: the photoelectric conversion efficiency of Comparative Example 1 of the encapsulating film is taken as the comparison standard of 100%, and the photoelectric conversion efficiency of the other encapsulating films is compared with it to calculate the improvement rate.
[0165] Photoelectric conversion efficiency improvement % = (Photoelectric conversion efficiency of the encapsulating film in the current example - Photoelectric conversion efficiency of the encapsulating film in Comparative Example 1) / Photoelectric conversion efficiency of the encapsulating film in Comparative Example 1 * 100%
[0166] Table 1
[0167] Example 1 of encapsulating film Polymer 2 94.08 0.84 67 Encapsulation film Example 2 Polymer 2 93.97 0.83 67 Encapsulation film Example 3 Polymer 2 94.10 0.92 70 Encapsulation film Example 4 Polymer 2 94.06 0.82 67 Encapsulation film Example 5 Polymer 13 94.16 0.95 66 Encapsulation film Example 6 Polymer 19 94.13 0.94 67 Encapsulation film Example 7 Polymer 30 94.05 0.89 68 Encapsulation film Example 8 Polymer 42 94.27 1.06 61 Encapsulation film Example 9 Polymer 51 94.19 0.98 65 Encapsulation film Example 10 Polymer 54 94.17 0.97 65 Encapsulation film Example 11 Polymer 57 93.94 0.85 69 Encapsulation film Example 12 Polymer 60 94.02 0.87 69 Encapsulation film Example 13 Polymer 63 94.28 1.09 61 Encapsulation film Example 14 Polymer 65 94.22 1.02 62 Encapsulation film Example 15 Polymer 72 94.17 0.99 63 Comparative Example 1 of Encapsulating Film Ref1 89.88 — 80 Comparative Example 2 of Encapsulation Film Ref2 88.96 0.52 81 Comparative Example 3 of Encapsulation Film Ref3 89.67 0.43 86
[0168] The results above show that when the polymer of the present invention is added to the film as an ultraviolet light conversion encapsulation film and applied to solar cell modules, it has high visible light transmittance, good absorption of ultraviolet light, and converts ultraviolet light into visible light, thereby significantly improving the conversion efficiency and weather resistance of solar photovoltaic modules.
[0169] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A polymer containing triazole, characterized in that, The polymer has the structure shown in formula (I). Equation (I), In equation (I), n is an integer between 1 and 100; X is -O-, -S-, -Se-, -S(O)2-, or -NR x -;R x Selected from C 1-12 Any one of alkyl, phenyl, and benzyl groups; R1 is selected from C 2-12 Alkyl, unsubstituted C 3-8 cycloalkyl, composed of C 1-6 At least one group in the alkyl group substituted with C 4-12 3-6 membered cycloalkyl groups; R 21 R 22 R 23 R 24 R 25 Each is independently selected from H, hydroxyl, and C. 1-12 alkyl groups, C groups substituted with at least one group from combination A 1-12 alkyl, C 1-12 alkoxy groups, R3COO-, R3CO-, C 2-12 At least one of alkenyl, (R3O)3Si-, and (R3O)3SiO-, where R3 is selected from C 1-12 alkyl, C 2-12 Any one of the alkenyl groups; the combination A consists of a halogen, a 3-6 membered cycloalkyl group containing at least one heteroatom selected from at least one of O, S, and N.
2. The triazole-containing polymer according to claim 1, characterized in that, In equation (I), n is an integer between 2 and 90; X is -O-, -S-, -Se-, -S(O)2-, or -NR x -;R x Selected from C 1-10 Any one of alkyl, phenyl, and benzyl groups; R1 is selected from C 2-10 Alkyl, unsubstituted C 3-6 cycloalkyl, composed of C 1-6 At least one group in the alkyl group substituted with C 4-10 3-6 membered cycloalkyl groups; R 21 R 22 R 23 R 24 R 25 Each is independently selected from H, hydroxyl, and C. 1-12 alkyl groups, C groups substituted with at least one group from combination A 1-12 alkyl, C 1-12 alkoxy groups, R3COO-, R3CO-, C 2-12 At least one of alkenyl, (R3O)3Si-, and (R3O)3SiO-, where R3 is selected from C 1-10 alkyl, C 2-10 Any one of the alkenyl groups; the combination A consists of fluorine, chlorine, bromine, or a 3-6 membered cycloalkyl group containing at least one O atom as a cycloforming atom.
3. The triazole-containing polymer according to claim 1 or 2, characterized in that, In equation (I), n is 4, 5, 6, 7 or 8; X is either -O- or -S-; R1 is selected from C 2-10 Alkyl, unsubstituted C 3-6 cycloalkyl, composed of C 1-6 At least one group in the alkyl group substituted with C 4-10 3-6 membered cycloalkyl groups; R 21 R 22 R 23 R 24 R 25 Each is independently selected from H, hydroxyl, and C. 1-12 alkyl groups, C groups substituted with at least one group from combination A 1-12 alkyl, C 1-12 alkoxy groups, R3COO-, R3CO-, C 2-12 At least one of alkenyl, (R3O)3Si-, and (R3O)3SiO-, where R3 is selected from C 1-10 alkyl, C 2-10 Any one of the alkenyl groups; the combination A consists of fluorine, chlorine, bromine, or a 3-6 membered cycloalkyl group containing at least one O atom as a cycloforming atom.
4. The triazole-containing polymer according to claim 3, characterized in that, The polymer represented by formula (I) is selected from any of the following, where n is independently 4, 5, 6, 7 or 8: 。 5. The triazole-containing polymer according to claim 1 or 2, characterized in that, In equation (I), n is 4, 5, 6, 7 or 8; X is either -Se- or -S(O)2-; R1 is selected from C 2-10 Alkyl, unsubstituted C 3-6 cycloalkyl, composed of C 1-6 At least one group in the alkyl group substituted with C 4-10 3-6 membered cycloalkyl groups; R 21 R 22 R 23 R 24 R 25 Each is independently selected from H, hydroxyl, and C. 1-12 alkyl groups, C groups substituted with at least one group from combination A 1-12 alkyl, C 1-12 alkoxy groups, R3COO-, R3CO-, C 2-12 At least one of alkenyl, (R3O)3Si-, and (R3O)3SiO-, where R3 is selected from C 1-10 alkyl, C 2-10 Any one of the alkenyl groups; the combination A consists of fluorine, chlorine, bromine, or a 3-6 membered cycloalkyl group containing at least one O atom as a cycloforming atom.
6. The triazole-containing polymer according to claim 5, characterized in that, The polymer represented by formula (I) is selected from any of the following, where n is independently 4, 5, 6, 7 or 8: 。 7. The triazole-containing polymer according to claim 1 or 2, characterized in that, In equation (I), n is 4, 5, 6, 7 or 8; X is -NR x -;R x Selected from C 1-10 Any one of alkyl, phenyl, and benzyl groups; R1 is selected from C 2-10 Alkyl, unsubstituted C 3-6 cycloalkyl, composed of C 1-6 At least one group in the alkyl group substituted with C 4-10 3-6 membered cycloalkyl groups; R 21 R 22 R 23 R 24 R 25 Each is independently selected from H, hydroxyl, and C. 1-12 alkyl groups, C groups substituted with at least one group from combination A 1-12 alkyl, C 1-12 alkoxy groups, R3COO-, R3CO-, C 2-12 At least one of alkenyl, (R3O)3Si-, and (R3O)3SiO-, where R3 is selected from C 1-10 alkyl, C 2-10 Any one of the alkenyl groups; the combination A consists of fluorine, chlorine, bromine, or a 3-6 membered cycloalkyl group containing at least one O atom as a cycloforming atom.
8. The triazole-containing polymer according to claim 7, characterized in that, The polymer represented by formula (I) is selected from any of the following, where n is independently 4, 5, 6, 7 or 8: 。 9. A polymer containing triazole, characterized in that, The triazole-containing polymer is selected from any one of the following, wherein n is independently 4, 5, 6, 7 or 8: 。 10. The use of the polymer according to any one of claims 1-9 in encapsulating adhesives.
11. The application of the polymer according to claim 10 in encapsulating adhesives, characterized in that, The encapsulating adhesive is an ultraviolet light conversion encapsulating adhesive.
12. A composition for encapsulating adhesive, characterized in that, The composition contains 100 parts by weight of matrix material, 0.005-2 parts by weight of ultraviolet light converter, 0-2 parts by weight of photoinitiator, 0.1-1 parts by weight of light stabilizer, 0-3 parts by weight of crosslinking agent, 0-2 parts by weight of co-crosslinking agent, 0.05-1 parts by weight of antioxidant and 0.2-1 parts by weight of silane coupling agent; The ultraviolet light converter is selected from the polymers described in any one of claims 1-9.
13. The composition for encapsulating adhesive according to claim 12, characterized in that, The matrix material is an ethylene-vinyl acetate copolymer.
14. The composition for encapsulating adhesive according to claim 13, characterized in that, The ethylene-vinyl acetate copolymer used as the matrix material contains 25-35 wt% vinyl acetate structural units, has a melt index of 0.1-40 g / min, a melting point of 40-90 °C, and a light transmittance of ≥90%.
15. A method for preparing an encapsulating adhesive, characterized in that, The method includes: curing material I containing each component of the composition to obtain the encapsulating adhesive; The composition is the encapsulating adhesive composition according to any one of claims 12-14.
Citation Information
Patent Citations
Polymer containing benzotriazole unit, preparation method thereof, and solar cell device
CN104211917A
Organic compound and application thereof, ultraviolet light conversion packaging adhesive film and preparation method thereof, and photovoltaic module
CN118026943A